Implications of COVID-19 Outbreak on Immune Therapies in Multiple Sclerosis Patients—Lessons Learned From SARS and MERS - Möhn, Nora; Pul, Refik; Kleinschnitz, Christoph; Prüss, Harald; Witte, Torsten; Stangel, Martin; Skripuletz, Thomas (Frontiers in Immunology, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic keeps the world in suspense. In addition to the fundamental challenges for the health care system, the individual departments must decide how to deal with patients at risk. Neurologists are confronted with the question, how they should advise their patients regarding immunosuppressive treatment. In particular, the large number of different disease-modifying therapies (DMTs) in the treatment of neuroimmunological diseases such as multiple sclerosis poses a challenge. Since there is scarce evidence on immunocompromised patients in the current outbreak, it makes sense to draw on the findings of previous coronavirus outbreaks, namely SARS- and Middle East respiratory syndrome (MERS) coronavirus outbreaks in 2002/2003 and 2012. Overall, immunosuppressive therapy does neither seem to have a major impact on infection with SARS- and MERS-CoV nor does it seem to lead to a severe disease course in many cases. Considering the immunological responses against infections with novel coronaviruses in humans, interferons, glatiramer acetate, and teriflunomide appear to be safe. As lymphopenia seems to be associated with a more severe disease course, all DMTs causing lymphopenia, such as cladribine, alemtuzumab, and dimethyl fumarate, need to be reviewed more thoroughly. Depleting anti-CD20 antibodies may be problematic drugs. They are, in general, associated with a higher risk of infection. The fact that they inhibit the production of neutralizing antibodies may be an additional problem. In summary, previous outbreaks have not shown an increased risk for immunocompromised patients. Patients with severe neuroimmunological diseases should be kept from hasty discontinuation of immunotherapy.